Managed alcohol: one community's innovative response to risk management during COVID-19 - Heidi Brocious; Kathi Trawver; LaVerne Xilegg Demientieff (BMC, 2021)
Abstract Background Harm reduction programs often lack community-based support and can be controversial, despite data demonstrating effectiveness. This article describes one small Alaskan community's development of a harm reduction managed alcohol program (MAP) in the context of a city-run quarantine site for individuals experiencing homelessness. The MAP was developed to support quarantining by COVID-19-exposed or COVID-positive individuals who also experienced chronic homelessness, a severe alcohol use disorder, and heightened health risks related to potentially unsupported alcohol withdrawal. Method Five interviews with key informants involved in planning or implementation of the MAP were conducted using rapid qualitative analysis and narrative analysis techniques. Outcome This study documents the planning and implementation of an innovative application of a managed alcohol harm reduction intervention in the context of the COVID-19 pandemic. In this instance, a MAP was used specifically to limit hospital admissions for alcohol withdrawal during a surge of cases in the community, as well as to mitigate spread of the virus. Key informants report no residents enrolled in the MAP program as a part of quarantine required hospitalization for withdrawal or for COVID symptoms, and no shelter resident left the quarantine site while still contagious with COVID-19. Additionally, the level of community support for the program was much higher than originally expected by organizers. Conclusions This program highlighted an example of how a community recognized the complexity and potential risk to individuals experiencing structural vulnerability related to homelessness and a severe AUD, and the community at large, and was able to create an alternative path to minimize those risks using a harm reduction strategy.